2017
DOI: 10.1111/jcmm.13324
|View full text |Cite
|
Sign up to set email alerts
|

cAMP response element‐binding protein and Yes‐associated protein form a feedback loop that promotes neurite outgrowth

Abstract: The cAMP response element‐binding (CREB) protein is a member of the CREB/activating transcription factor family that is activated by various extracellular stimuli. It has been shown that CREB‐dependent transcription stimulation plays a key role in neuronal differentiation and plasticity, but the underlying mechanisms remain largely elusive. Here, we show that Yes‐associated protein (YAP) is a direct target induced by CREB upon retinoic acid (RA)‐induced neurite outgrowth stimuli in N2a cells. Interestingly, YA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…Importantly, introduction of a miR-375 mimic significantly reduced colony formation, EdU incorporation, and migration, indicative of reduced survival, proliferation, and metastatic potential, respectively. Previous studies have reported interactions between YAP1 and CREB,45, 46 a key mediator of cAMP/PKA signaling, including in liver cancer. CREB transcriptionally activates YAP1, whereas YAP1 promotes protein stability of CREB.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, introduction of a miR-375 mimic significantly reduced colony formation, EdU incorporation, and migration, indicative of reduced survival, proliferation, and metastatic potential, respectively. Previous studies have reported interactions between YAP1 and CREB,45, 46 a key mediator of cAMP/PKA signaling, including in liver cancer. CREB transcriptionally activates YAP1, whereas YAP1 promotes protein stability of CREB.…”
Section: Discussionmentioning
confidence: 99%
“…The Yes-associated protein (YAP) is one of the core effectors of the Salvador–Warts–Hippo (or simply Hippo) signaling pathway, and the other core effector is the transcriptional co-activator with a PDZ-binding motif (TAZ) [ 57 ]. In normal organ tissues, the Hippo/YAP pathway functions to regulate organ size growth control, stem cell function, and regeneration [ 16 , 57 , 58 ]. Deregulation of the Hippo pathway and hyperactivation of YAP are frequently found in a diverse range of cancers, and the Hippo/YAP pathway has been suggested to be involved in cancer initiation and progression [ 16 , 57 ].…”
Section: Hippo/yap Singing Pathway In Nsclcmentioning
confidence: 99%
“…Overexpression of YAP has been found in many cancers because of abnormal amplification, loss of Hippo signaling by mutation, and/or downregulation of the core Hippo components. YAP has shown a correlation with stem cell renewal and differentiation, a crucial step in oncogenic transformation [36], and was reported to promote cancer development in various cancers [37,38,39,40].…”
Section: Yes-associated Protein In Human Nsclc and Mpmmentioning
confidence: 99%